Construction of a Practical Oriented Tool for Evaluating the Ability of Community Medical Staff to Provide Hospice Care Services and Its Reliability and Validity - SHA Jingjing, JING Limei, DING Tongjiu, XIN Yurong, TANG Lan, LI Shuijing (Zhongguo quanke yixue)
Background Hospice care service has been practiced deeply in our country. Many cities have taken primary medical and health institutions as the prime places to carry out hospice care, such as in Shanghai. The main community hospice care service are provided by the teams which are composed of general practitioners and nursing staff. Meanwhile, there is still a lack of unified assessment standards and requirements for the abilities of community medical staff. Objective Based on the actual situation hospice care service, this study compilies an evaluation tool for the hospice care service ability of medical staff in community health service centers and conducts a research of the reliability and validity. Methods From June 2022 to March 2023, through literature review, qualitative interview and two rounds of Delphi expert consultation, the project was tested by a questionnaire and analyzed. 1 281 medical staff of community health service centers in Pudong New Area, Shanghai, China, were surveyed from 2023-04-01 to 2023-05-12. A questionnaire survey which was covering general information, knowledge and experience of hospice service. Hospice service competence evaluation tool and humanistic care competence scale were conducted to test the reliability and validity of the hospice service, and a multiple linear regression analysis was used to explore the influencing factors of hospice service competence. Results Through literature search analysis and qualitative interviews with experts, 49 initial entries were formed. The Delphi expert consultation method invited a total of 15 authoritative experts in Shanghai who study and carry out hospice services, in which the expert authority coefficient was 0.87, and the Kendall harmony coefficient of the overall index system was 0.624 (P<0.01), and the evaluation tools for the 50 entries were finally formed after two rounds of Delphi expert consultation. A total of 1 300 questionnaires were distributed in the questionnaire survey part, and 1 284 questionnaires were recovered, the effective recovery rate of the questionnaires was 98.77% (1 284/1 300). The reliability coefficient of standardized evaluation tools was 0.993 with Cronbach's α coefficient. The data of Spearman-Brown's broken half reliability was 0.935, that means the overall reliability coefficient is good. Besides, KMO value was 0.987, Bartlett spherical value was 119 119.104, P<0.001, indicating that the scale had a good validity and was suitable for factor analysis. Factor analysis showed that the factor loading of all items was≥0.4 and the commonality was >0.2, so all 50 items were retained. Four common factors were selected, and the cumulative variance contribution rate was 86.517%. Correlation analysis showed that there was a significant positive correlation between the total score of the hospice care service ability evaluation tool constructed in this study and the total score of the humanistic care scale (r=0.819, P<0.001), indicating that the evaluation tool had a good calibration correlation validity. The results of multiple linear regression analysis showed that: gender, education, years of working in the community, whether or not they experienced the death of a relative, whether or not they experienced hospice training, the length of hospice service work, and whether or not they were willing to engage in hospice service were the influencing factors of hospice service competence (P<0.05) . Conclusion In this study, it proofs that the questionnaire tool for evaluating the ability of community health service center medical staff is scientific, reliability, and validity, and can be used to evaluate the various abilities of community general practitioners in hospice care services.